COMPUTED TOMOGRAPHY FOR THE DIAGNOSIS OF MULTICENTRIC LYMPHOMA IN A LABRADOR RETRIEVER - M, Takahira; Aptekmann, K.P; Zhang , E. D (International Journal of Allied Sciences (IJAS), 2022)
This study aims to demonstrate the potential of computed tomography (CT) as a valuable diagnostic tool for multicentric lymphoma in a 5-year-old female Labrador retriever weighing approximately 27 kg. The dog was brought to the Small Animal Medicine outpatient unit of Madras Veterinary College due to inappetance, generalized lymphadenopathy, and impaired vision. Preliminary diagnostic tests such as radiography, ultrasonography, and fine needle aspiration cytology (FNAC) of the lymph node suggested lymphoma. To confirm the diagnosis, a CT scan was performed on the patient under mild anesthesia. The CT scan revealed significant changes in the spleen and other abdominal organs, confirming the presence of multicentric lymphoma. Compared to traditional X-ray imaging, CT offers several advantages for diagnosing this condition. By providing cross-sectional images of internal organs, CT allows for more accurate and comprehensive evaluation of the affected areas. Conventional X-ray imaging is limited in this regard due to the superimposition of structures. In conclusion, this case study highlights the importance of incorporating CT scans into the diagnostic process for multicentric lymphoma in dogs. The ability to obtain detailed cross-sectional images of internal organs can significantly improve the accuracy of the diagnosis, ultimately leading to more effective treatment and better patient outcomes